Tears of the sun - Fuqua, Antoine; Lasker, Alex; Cirillo, Patrick (Columbia TriStar Home Entertainment ; distributed in the Philippines by MagnaVision, 2003)
When a doctor is rescued by a Special-Ops unit in the jungle of Nigeria, she refuses to go with them unless they agree to help rescue 70 refugees as well.